The Relationship Between Personality Traits (Neuroticism and Extraversion) and Self-Efficacy With Aging Depression - Mohammad Abbasi; Fazlollah Mirderikvand; Hamide Adavi; Mohammad Hojati (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives  This study aimed to analyze the relationship personality traits (neuroticism and extraversion) and self-efficacy with aging depression in retiree male teachers in Harsin City, Iran.  Methods & Materials The present study followed a cross-sectional descriptive correlation method. In this research, a total of 173 retiree male teachers in Harsin were selected by random sampling method. Research tools included geriatric depression scale, NEO five-factor inventory and generalized self-efficacy scale.  Results The obtained information was separately analyzed by Pearson correlation coefficient and regression. This research showed significant negative associations between aging depression with extraversion (r=-0.65, P<0.001), and self-efficacy (r=-0.66, P<0.001). There were also significant positive correlation between neuroticism (r=0.54, P<0.001) and aging depression.  Conclusion Neuroticism can affect aging depression of retiree male teachers. And more extraversion and self-efficacy can result in decrease in depression of retiree male teachers.